Engaging youth in policy processes on agriculture and agribusiness - Shitaatala, Eva; Mabonga, Lilian; Adedeji, Oluwaseun; Nsanganira, Tony R. (Technical Centre for Agricultural and Rural Cooperation, 2019)
The recent CTA workshop on ‘facilitating next-generation ACP agriculture through youth entrepreneurship, job creation and digitalisation’ identified seven critical success factors for successful rural entrepreneurship and job creation: access by youth to investment and finance, scalable approaches and models that can be taken up, enabling policy environments for youth, agriculture that is attractive to youth, access by youth to markets, business models that work, and access to a pool of appropriate skills, capacities and knowledge and ways to grow these.